Enhancing phenol removal from waste water by adding powder activated carbon to the lab-scale activated sludge system - Nguyen My Linh; Nguyen Duy Dat (Journal of Technical Education Science, 2021)
In this study, the commercial powder activated carbon (PAC) was added to a bench scale conventional activated sludge (CAS) system to enhance phenol removal. The mixed liquor suspended solid (MLSS) concentration of CAS with adding PAC was stable in all stages of operation, while MLSS concentrations in CAS without PAC addition sharply decreased as the Phenol loading reached 1.8 g phenol/L.day. Higher removal of chemical oxygen demand (COD) and Phenol achieved with the CAS by PAC addition compared with those achieved with CAS without PAC addition. The difference in COD removal efficiency was 7 - 9% in stages 3 and 4 (0.8 and 1.2 g phenol/L.day, respectively), and about 33% in stage 5 (1.8 g phenol/L.day). The advantage of CAS with PAC addition was clearly observed in the highest phenol loading (1.8 g phenol/L.day) because the MLVSS/MLSS ratio of CAS with PAC addition increased and the COD and phenol removal efficiencies kept stable in this stage, while reverse trends were found for CAS without PAC addition. The results indicated that the adaptive ability of the CAS by adding PAC was significantly higher than the CAS without AC addition. This study offers useful preliminary results for applying a hybrid system between CAS and adsorption with PAC for further research and application in future.